Juergen Voegele, IPCC WGIII release, April 16, 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Juergen Voegele, Welcome Address Meeting global food needs with lower emissions: IPCC report findings on climate change mitigation in agriculture A dialog among scientists, practitioners and financiers April 16, 2014 World Bank, Washington, DC